Inflation and speculation in a dynamic macroeconomic model - Matheus R. Grasselli; Adrien Nguyen Huu (Journal of Risk and Financial Management, 2015)
We study a monetary version of the Keen model by merging two alternative extensions, namely the addition of a dynamic price level and the introduction of speculation. We recall and study old and new equilibria, together with their local stability analysis. This includes a state of recession associated with a deflationary regime and characterized by falling employment but constant wage shares, with or without an accompanying debt crisis.
Keywords: 330; Minsky's financial instability hypothesis; debt-deflation; Keen model; stock-flow consistency; financial crisis; dynamical systems in macroeconomics; local stability